Spontaneous Otogenic Pneumocephalus due to Frequent Plane Travelling - Katherine Pollaers; Jafri Kuthubutheen (Case Reports in Otolaryngology)
A 31-year-old male presented with a history of chronic right-sided facial and mastoid tip pain with associated tinnitus and hearing loss. These symptoms were aggravated by the regular aeroplane trips he made to work as a “fly-in, fly-out” worker in regional Australia. Imaging revealed significant pneumocephalus secondary to mastoid air cell defects, which were repaired via a transmastoid approach. This is the fourth case of spontaneous otogenic pneumocephalus associated with air travel at altitude reported in the literature. This case is remarkable for the chronic nature of the symptoms, which were aggravated by the patient’s regular aeroplane travel. This has implications for occupations which require frequent flying in those patients who may be at risk.